Drug interactions with angiotensin-converting enzyme inhibitors: Interakcije zdravil z zaviralci angiotenzinske konvertaze - Pal, Marjetka; Ferk, Polonca (Acta Medico-Biotechnica, 2021)
We reviewed potentially clinically significant drug–drug interactions (DDIs) with angiotensin-converting enzyme inhibitors (ACEIs) using Stockley’s Drug Interactions books and two online DDI databases. We identified >10 such DDIs and described their mechanisms, clinical evidence and importance, as well as their management. Most DDIs with ACEIs were pharmacodynamic; only a few were pharmacokinetic. Most DDIs with ACEIs involved drugs that can lead to excessive reduction of blood pressure, hyperkalemia and impaired renal function. There is some evidence linking ACEIs with the induction of lithium toxicity. Severe hypersensitivity reactions may occur in patients treated with ACEIs with concomitant use of allopurinol or parenteral applications of iron. ACEIs should be combined carefully with hepatotoxic drugs due to their own potential hepatotoxic effects. The prevalence of adverse drug reactions due to DDIs might be high because they are prescribed frequently. Fortunately, most of such DDIs can be managed by clinical and laboratory monitoring of patients or by dosage adjustments of concomitantly used drugs.